Fixed-term contracts and wages revisited using linked employer-employee data - Christian Pfeifer (Journal for Labour Market Research, 2012)
This empirical research note uses linked employer-employee data from the German Federal Statistical Office to estimate wage differentials between workers with fixed-term contracts and permanent contracts. The data set allows to analyze wage differentials within firms and across the wage distribution. The main findings are: (1) Worker characteristics account for about half of the unconditional mean wage differential. The wage disadvantage of workers with fixed-term contracts is further reduced by the inclusion of occupations and firm fixed effects to approximately ten percent. (2) The wage disadvantage is larger at the lower tail of the wage distribution and quite constant in the middle and upper parts of the wage distribution.
Keywords: J31; J41; 330; Lohnunterschied; befristeter Arbeitsvertrag; unbefristeter Arbeitsvertrag; interner Arbeitsmarkt; dualer Arbeitsmarkt; Lohnstruktur; Lohndiskriminierung